Sulfasalazine induced lung toxicity masquerading as sarcoidosis - case report and review of the literature - Mohyuddin, Ghulam Rehman; Sultan, Fatima; Zhang, Kai; Khaleeq, Ghulam (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
A commonly prescribed drug for Rheumatoid Arthritis (R.A) and Inflammatory Bowel Disease (IBD) treatment, Sulfasalazine can occasionally cause lung toxicity such as interstitial pneumonitis and eosinophilic pneumonias. We report a case of a 46 year old female being treated with Sulfasalazine for Ulcerative Colitis, who developed shortness of breath and a radiographic pattern of hilar adenopathy. Biopsy showed granulomas that resembled Sarcoidosis. We review different presentations of Sulfasalazine induced lung disease and describe the first known case of Sulfasalazine lung toxicity mimicking Sarcoidosis.